Intensive Case Study Methodology for the Analysis of Self-Help Housing Consolidation, Household Organization and Family Mobility - Ward, Peter M. (2014)
The paper describes an innovative methodology developed as part of a major “mixed methods” collaborative and multidisciplinary research project across several Latin American cities. It offers a systematic “hands-on” methodology about how to conduct multi-disciplinary and team-based intensive case studies of low-income household dynamics and trajectories in self-help dwelling structures in (now) consolidated low-income settlements of Latin America. The research project describes how to collect information about family genealogies, household organization and individual member mobility, tied to materials that allow for the construction of detailed housing plans and architectonic diagrams resulting from self-building in informal settlements over a thirty-year period. The majority of the original “owner” self-builders still reside in these (now) consolidated properties, and the methodology provides for cross generational analysis of household behavior in relation to the dynamics of dwelling construction and use of space, household organization, inheritance and heirship.